Islamic Counseling Communication of Nurses on Cancer Patients in Islamic Hospital - Siti Sumijati; Dyah Rahmi Astuti; Asep Iwan Setiawan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This study aims to determine the therapeutic communication of Islamic perspectives conducted by nurses in cancer patients in Islamic Hospitals. The research was conducted through a qualitative approach with the study of symbolic interactionism. The results showed that the communication management carried out by RSI nurses in chemotherapy patients was carried out with an interpersonal approach, the use of persuasive sentences, empathic communication of patients' families, and trancedental communication. The meaning of verbal communication is done when providing relevant information to patients and collecting patient data. The meaning of non-verbal communication is done to read the patient's emotions through facial expressions and intonation. The symbolic interaction process can be seen when nurses treating chemotherapy patients have fear or worry when interacting with their patients.Penelitian ini bertujuan untuk mengetahui komunikasi terapeutik perspektif Islam yang dilakukan oleh perawat pada pasien kanker di Rumah Sakit Islam. Penelitian dilakukan melalui pendekatan kualitatif dengan studi interaksionisme simbolik. Hasil penelitian menunjukkan bahwa pengelolaan komunikasi yang dilakukan para perawat RSI pada pasien kemoterapi dilakukan dengan pendekatan interpersonal, penggunaan kalimat persuasif, komunikasi empatik keluarga pasien dan komunikasi transedental. Makna komunikasi verbal dilakukan pada saat memberikan informasi penting kepada pasien dan mengumpulkan data pasien. Makna komunikasi non verbal dilakukan untuk membaca emosi pasien baik melalui ekspresi wajah maupun intonasi. Proses interaksi simbolik dapat dilihat pada saat perawat merawat pasien kemoterapi memiliki rasa takut atau khawatir pada saat berinteraksi dengan pasiennya.